Tackling Control of a Cosmopolitan Phytopathogen: Sclerotinia - O’Sullivan, Cathryn A.; Belt, Katharina; Thatcher, Louise F. (Frontiers in Plant Science, 2021)
Phytopathogenic members of the Sclerotinia genus cause widespread disease across a broad range of economically important crops. In particular, S. sclerotiorum is considered one of the most destructive and cosmopolitan of plant pathogens. Here were review the pathogen’s epidemiology, its economic impact on agricultural production, and measures employed towards control of disease. We review the broad approaches required to tackle Sclerotinia diseases including cultural practices, crop genetic resistance, chemical fungicides and biological controls. We highlight the benefits and drawbacks of each approach along with recent advances within these controls and future strategies.